Optimal design of Cosine Modulated Filter Banks using quantum-behaved particle swarm optimization algorithm - Fangqing Tan; Tianqi Zhang; Chunxia Gao; Liechao Huang (2011 4th International Congress on Image and Signal Processing, 2011)
In the paper, a new method for designing Cosine Modulated Filter Banks (CMFB) is proposed, the prototype filter is designed by optimization method. Firstly, the method appropriately relaxes the limit conditions for perfect reconstruction, the design problem of CMFB is formulated as a nonlinear and unconstrained optimization of an objective function, which stopband cutoff frequency is fixed, passband cutoff frequency is adjusted to minimize the cost function which satisfies reconstruction condition, and directly designs the prototype filter. The simulation results illustrate the proposed method and its improvement over other methods in terms of amplitude distortion, aliasing distortion, signal to noise ratio and reconstruction performance.